Seismic vulnerability assessment and earthquake response of slender historical masonry bell towers in South-East Lombardia. (November 2021) - Valente, Marco
Highlights: Seismic assessment and earthquake response of slender historical masonry bell towers. Seismic response is affected by the main geometrical features and main vibration properties of the bell towers. Damage distribution among the different parts of the bell towers for different PGA values. Influence of different accelerograms on the energy density dissipated by tensile damage and maximum top displacements. Main limitations of the simplified approach are highlighted through a comparison with non-linear dynamic analyses. Abstract: Masonry bell towers represent a large portion of the Italian cultural heritage and are highly vulnerable to seismic actions mainly due to their relevant slenderness, as also observed in recent seismic events. The present study investigates the seismic vulnerability and earthquake response of five slender historical masonry bell towers, which are located in South-East Lombardia (Northern Italy), through a preliminary simplified procedure suggested by the Italian Code and advanced numerical simulations. To thoroughly study the seismic response of the bell towers, detailed three-dimensional FE models with a damage plasticity constitutive law for masonry are developed and non-linear dynamic analyses are performed using different accelerograms. The results of the non-linear dynamic analyses show that the geometrical features and the main vibration properties of the bell towers turn out to be the main parameters influencing the seismic performance of such a construction typology. Moreover, it can be noted a clear influence of the accelerograms characteristics on both the energy dissipated by tensile damage and the maximum normalized displacements of the bell towers. On the other hand, the structural geometrical characteristics play a very important role in terms of damage distribution among the different parts of the bell towers. In addition, the main limitations of the simplified approach suggested by the Italian Code for the seismic assessment of the bell towers under study are highlighted through a comparison with the results obtained from non-linear dynamic analyses. The main outcomes presented in this study may also represent a useful insight to better understand the earthquake response and seismic vulnerability of similar masonry bell towers located in the same region, providing valuable information that can be directly used in seismic risk assessment at regional scale.